The effect of papaya leaf extract (Carica papaya) with concentration on egg hatchability of nile tilapia (Oreochromis niloticus) - Saputry, Afifa Muning; Latuconsina, Husain; Lisminingsih, Ratna Djuniwati (Sangia Research Media and Publishing, 2023)
Delays in hatching of fish eggs are influenced by several factors such as water quality instability during rearing, including; temperature, DO, pH. Papaya leaf is one of the plants that can be used to accelerate the hatchability of fish eggs. Papaya itself can be used as a component to boost the immune system because it contains the enzyme papain. The purpose of this study was to compare the hatchability of nile tilapia (Oreochromis niloticus) eggs in the treatment of papaya leaf extract (Carica papaya) with different doses. This research was conducted at the Punten Cultivation Fisheries Installation, Batu City in December 2022. Using a Completely Randomized Design (CRD) where there were 4 treatments, namely: A) papaya leaf extract 4 mL/L, B) papaya leaf extract 6 mL/L, C ) papaya leaf extract 10 mL/L, and D) control without treatment. In each treatment there were 3 repetitions. The ANOVA test was used to compare the effect of papaya leaf extract on hatchability of tilapia eggs, and was followed up with the BNT test if there were significant differences in the treatments. The results showed that there were significant differences in the treatment with the addition of papaya leaf extract on the hatchability of tilapia eggs, with 4 mL/L treatment) being the best treatment in increasing the hatchability percentage of tilapia eggs by 88.33%. There is a tendency that the higher the papaya leaf extract, the egg hatchability decreases.